What we know: solutions from our experiences in the justice system - Nixon, Vivian; Atkinson, Daryl V. (The New Press, 2020)
Machine generated contents note:1.Earmark Jobs to Reduce Recidivism /Kevin E. Jackmon --2.A Tiny Ray of Light: On the Need for an Authentic Oversight Regime Within the Texas Department of Criminal Justice /Thomas Bartlett Whitaker --3.Unlock Digital Inclusion /Teresa Y. Hodge --4.On Prison Labor /Ty Evans --5.Correcting Excessive Sentences of Youthful Offenders /Aaron Striz --6.An Act to Increase Voter Registration and Participation /Corey "Al-Ameen" Patterson --7.On Honor Yards /C.T. Mexica --8.Undebatable /Daniel S. Throop --9.A Call for Pardons /Khalil A. Cumberbatch --10.Over-Incarceration and Gain Time: What's Wrong and How to Fix It /Jeremiah Paul Cahours --11.From Coming Home to Running the Homecoming Project /Terah Lawyer --12."Life" Means Death /Reginald Manning --13.The 13th and the Problem of the Color Line /Mika'il DeVeaux --14.From the Ground Up: Tapping the Strengths of Incarcerated People /Matheiv Lucas Ayotte --15.A Bridge to Employment /Michelle Jones --16.Closing the Literacy Gap /Sreedhar Potarazu --17.The Age of Inequality: Ending the Mass Incarceration of Our Youth /Chris Dankovich --18.Prisons as Nursing Homes: A Taxpayer Debacle /Charles Patrick Norman --19.In Defense of Survival: Incentivizing Good Behavior /Shirley Anne McCulley --20.Electoral Politics: The New Revolution /Lewis Conway Jr. --21.Wards of the State /Arthur Longworth --22.Mass Incarceration and Small Business /Bob Pelshaw --23.A New North Star /DeAnna Hoskins.